Accuracy of Subjective Performance Appraisal is Not Modulated by the Method Used by the Learner During Motor Skill Acquisition. Issue 2 (April 2016) - Patterson, Jae T.; McRae, Matthew; Lai, Sharon
The present experiment examined whether the method of subjectively appraising motor performance during skill acquisition would differentially strengthen performance appraisal capabilities and subsequent motor learning. Thirty-six participants (18 men and 18 women; M age = 20.8 years, SD = 1.0) learned to execute a serial key-pressing task at a particular overall movement time (2550 ms). Participants were randomly separated into three groups: the Generate group estimated their overall movement time then received knowledge of results of their actual movement time; the Choice group selected their perceived movement time from a list of three alternatives; the third group, the Control group, did not self-report their perceived movement time and received knowledge of results of their actual movement time on every trial. All groups practiced 90 acquisition trials and 30 no knowledge of results trials in a delayed retention test. Results from the delayed retention test showed that both methods of performance appraisal (Generate and Choice) facilitated superior motor performance and greater accuracy in assessing their actual motor performance compared with the control condition. Therefore, the processing required for accurate appraisal of performance was strengthened, independent of performance appraisal method.